Immunosuppressive adenosine-targeted biomaterials for emerging cancer immunotherapy - Wei, Qi; Zhang, Lening; Zhao, Nan; Cheng, Zhihua; Xin, Hua; Ding, Jianxun (Frontiers in Immunology, 2022)
Immunotherapy has paved the way for the future of cancer therapy, but there are still significant challenges to be overcome, such as the occurrence of immune escape or suppression. Adenosine is essential in modulating the immune responses of immune cells and maintaining immune tolerance. Emerging adenosine pathway inhibitors are considered a breakthrough in cancer immunotherapy, with emphasis first being placed on the top-down blockade of adenosine signaling axis, followed by combination therapy. However, these therapeutic strategies rely on adenosine inhibitors, mainly small molecules or antibody proteins, which are limited by a single route of administration and off-target toxicity. Therefore, synergistic nanomedicine with accurate delivery targeting deeper tumors is focused on in preclinical studies. This review discusses how adenosine reshapes immunosuppressive microenvironments through its effects on immune cells, including lymphocytes and myeloid cells. Additionally, it will be the first discussion of a comprehensive strategy of biomaterials in modulating the adenosine signaling pathway, including inhibition of adenosine production, inhibition of adenosine binding to immune cells, and depletion of adenosine in the microenvironments. Furthermore, biomaterials integrating multiple therapeutic modalities with adenosine blocking are also discussed as a promising strategy for promoting cancer immunotherapy.